Модель безконтактної електричної машини зі збудженням від постійних магнітів - Макарчук, О.В. (Технічна електродинаміка, 2011)
The mathematical model of electromechanical system "the contactless electric machine – the position rotor sensor – semiconductor rectifier or inverter" is considered. The comparative analysis of calculation results and experimental data is made.